Avoidance behavior towards digital crowd sourcing platforms: a preliminary study among new freelancers / Sharidatul Akma Abu Seman …[et al.] - Abu Seman, Sharidatul Akma; Shahrom, Melissa; Mohd, Idaya Husna; Tuan Besar, Tuan Badrol Hisham (Universiti Teknologi MARA, 2021)
New innovations and the expansion of the Internet have led to a rising trend in crowd sourcing platforms, which has, in turn, changed the business model from face-to-face services to platform-based services. This trend heavily relies on digital experts and skilled users in an interconnected ecosystem. While the literature has widely discussed the concepts and benefits of digital crowd sourcing towards employers and employees, the majority of today's crowd sourcing platforms face challenges and various potential threats, especially among newcomers in this digital world. The work investigates the perceived threats towards the avoidance motivation and avoidance behavior among newcomers to digital crowd sourcing platforms. An online survey was performed using Structural Equation Modelling (SEM) among 142 newly-registered students who were actively involved in the digital workforce climate. The statistical results confirmed that avoidance motivation leads to avoidance behavior, while perceived threats and self-efficacy lead to perceived threats. Additionally, perceived threats are influenced by perceived severity. Contradictory, perceived threats did not significantly influence perceived susceptibility. The findings are useful not only for digital crowd sourcing platforms but also for policymakers.